Lentiginosis in quadrant distribution - Kopera, D... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1997)
A 34-year-old woman with numerous lentigines in a quadrant distribution scattered over the lower right portion of her body is presented. Removal of multiple lentines may be crucial. A safe and effective method for the removal of multiple lentigenes is shown. Differential diagnoses of this unusual distribution pattern of lentigines are discussed. Argon laser treatment has been initiated for the management of this pigmentary disorder for cosmetic reasons. Lentigines faded within 4 weeks after application of 2 to 4 argon laser light impulses each. Quadrant distribution of skin lesions represents a rare pattern due to mosaicism in early embryogenesis. Treatment of lentigines with argon laser can be regarded as an effective approach in the management ofmultiple lentigines leading to an excellent cosmetical results.
Keywords: Adult; Diagnosis; Lasers; Lentigo; Therapy